Enteritis associated with Clostridium difficile and opportunistic candidiasis in a foal - Preis, Ingred S.; Silva, Rodrigo O. S.; Pires, Prhiscylla S.; Lobato, Francisco C. F.; Palhares, Maristela S.; Maranhão, Renata P. A.; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2012)
A twelve-day-old foal was admitted to the Veterinary School of UFMG with profuse diarrhea. The animal was treated with several medications, including antibiotics. Despite the clinical care, the clinical condition did not improve. Due to poor prognosis, the foal was euthanized. Gross and histopathological examinations, showed pseudomembranous and/or membranous glossitis, esophagitis and gastritis with intense amount of pseudohyphae and blastoconidia compatible with Candida spp Also, fibrinous and necrotizing typhlocolitis was observed. Clostridium difficile was isolated from intestinal contents which were also positive for toxins A/B by ELISA. Using a multiplex-PCR assay, genes encoding toxin A (tcdA) and toxin B (tcdB) were detected. The severe lesions caused by Candida in this foal probably occurred due to changes in the microbiota induced by the treatment with antibiotics. However, the possibility of an acquired immunodeficiency cannot be excluded because information about quantity and quality of the colostrum ingested by this foal was not obtained.